ANALYSIS OF FUZZY LOGIC CONTROLLER FOR TRANSFORMER-LESS VOLTAGE QUADRUPLER BOOST CONVERTER - Ramasamy A, M Balasubramanian, R DanielRaj (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The work focused on the development of a transformer-less adjustable voltage Quadrupler DC Boost Converter with Fuzzy Logic Controller to enhance high-voltage transfer gain and reduced semiconductor voltage stress is proposed. The proposed topology utilizes input-parallel output-series configuration for providing a much higher voltage gain without adopting an extreme large duty cycle. The projected converter cannot only achieve high step-up voltage gain with reduced number of component. It also reduces the voltage stress of both active switches and diodes. This will allow to choose lower voltage rating of IGBTs and diodes to reduce both switching and conduction losses. Closed loop Fuzzy Logic Controller is used to achieve the desired output voltage. The operation principle and steady analysis as well as a comparison with other recent existing high step-up topologies are presented. Experimental and simulation and results are presented to demonstrate the effectiveness of the proposed converter.